Enactive Management: A Nurturing Technology Enabling Fresh Decision Making to Cope with Conflict Situations - Garcia-De la Cerda, O (Elsevier Ltd, 2018)
The focus of this paper is observation, self-observation, and enactive management of organizational conflict situations whereby a community, an organization, or a human being has the possibility of recognizing their resources and generating changes in their practices if they so desire, and making fresh decisions, in the sense that different ontological dimensions are involved. We show how considering Body1- Language- Emotions- History- Eros- Silence can configure a nurturing technology call CLEHES. This tool has been applied for diverse people, groups, communities, and organizations that need and wish to develop their own skills to inquire conflict practice resolutions, in order to learn as a human decision support system. Conflict situations are understood as interactions, a breakdown in-between CLEHES from the individual or social standpoints. This tool allows observing the boundaries of conflict situations and building an observer system with the ability to manage, solve, or attenuate the situation, enabling fresh decision-making attending to the context in which the organization moves. This learning process happens in a constructed place called an Enactive Laboratory where strategies are developed to cope with the domains and context in the perceived individual and human activities systems. We present a case study focusing on a Learning Family Mediators System. © 2018